Information presentation format moderates the unconscious-thought effect: The role of recollection. Issue 8 (13th September 2016) - Abadie, Marlène; Waroquier, Laurent; Terrier, Patrice
ABSTRACT: The unconscious-thought effect occurs when distraction improves complex decision-making. In two experiments using the unconscious-thought paradigm, we investigated the effect of presentation format of decision information (i) on memory for decision-relevant information and (ii) on the quality of decisions made after distraction, conscious deliberation or immediately. We used the process-dissociation procedure to measure recollection and familiarity. The two studies showed that presenting information blocked per criterion led participants to recollect more decision-relevant details compared to a presentation by option. Moreover, a Bayesian meta-analysis of the two studies provided strong evidence that conscious deliberation resulted in better decisions when the information was presented blocked per criterion and substantial evidence that distraction improved decision quality when the information was presented blocked per option. Finally, Study 2 revealed that the recollection of decision-relevant details mediated the effect of presentation format on decision quality in the deliberation condition. This suggests that recollection contributes to conscious deliberation efficacy.